NiFe(C2O4)x as a heterogeneous Fenton catalyst for removal of methyl orange. (1st May 2017) - Liu, Yucan; Zhang, Guangming; Chong, Shan; Zhang, Nan; Chang, Huazhen; Huang, Ting; Fang, Shunyan
Abstract: This paper studies a heterogeneous Fenton catalyst NiFe(C2 O4 )x, which showed better catalytic activity than Ni(C2 O4 )x and better re-usability than Fe(C2 O4 )x . The methyl orange removal efficiency was 98% in heterogeneous Fenton system using NiFe(C2 O4 )x . The prepared NiFe(C2 O4 )x had a laminated shape and the size was in the range of 2–4 μm, and Ni was doped into catalyst's structure successfully. The NiFe(C2 O4 )x had a synergistic effect of catalyst of 24.7 for methyl orange removal, and the dope of Ni significantly reduced the leaching of Fe by 77%. The reaction factors and kinetics were investigated. Under the optimal conditions, 0.4 g/L of catalyst dose and 10 mmol/L of hydrogen peroxide concentration, 98% of methyl orange was removed within 20 min. Analysis showed that hydroxyl radicals and superoxide radicals participated in the reaction. With NiFe(C2 O4 )x catalyst, the suitable pH range for heterogeneous Fenton system was wide from 3 to 10. The catalyst showed good efficiency after five times re-use. NiFe(C2 O4 )x provided great potential in treatment of refractory wastewater with excellent property. Highlights: NiFe(C2 O4 )x catalyzed like-Fenton reaction achieved 98% methyl orange removal. The rate constant was 3.9 min −1 and the synergistic effect of catalyst was 24.7. The catalyst worked effectively in a wide range of pH from 3 to 10. Ni was doped into the catalyst and Fe leaching from catalyst was decreased by 77%. NiFe(C2 O4 )x showed good catalytic activity and re-usability.